Razing hell : rethinking everything you've been taught about God's wrath and judgment - Baker, Sharon L., 1956- (Louisville, Ky. : Westminster John Knox Press, 2010)
The author challenges the idea of punishment and the prospect of eternal damnation for Christians, examining biblical texts to challenge traditional assertions about the afterlife promised to sinners, and discussing alternatives that align more to the view of a gentle and loving God.
The landscape -- The image of God -- The justice of God -- The forgiveness of God -- Rethinking the violence of God -- Rethinking the image of God -- Rethinking the justice of God -- Rethinking the forgiveness of God -- The fire, the wicked, and the redeemed -- Outer darkness, gnashing of teeth and the lake of fire -- The Savior -- How then shall we live?
Includes bibliographical references and indexes.
Keywords: Hell -- Christianity; God (Christianity) -- Attributes; Hell -- Biblical teaching; God -- Biblical teaching